2017
DOI: 10.1021/acs.jced.7b00591
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurement of CO2 Solubility in Aqueous CaCl2 Solution at Temperature from 323.15 to 423.15 K and Pressure up to 20 MPa Using the Conductometric Titration

Abstract: In the framework of the efforts of the scientific community developed for the reduction of CO2 emissions, the geological storage of CO2 in deep saline aquifers is under focus. An increase of salinity decreases the potential of CO2 solubilization into the water. In salty waters, the salinity is not only due to NaCl but also to others ions and in particular Ca and Mg. Experimental solubility data of CO2 in calcium chloride solution available in the literature at conditions relevant to carbon storage are particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 14 publications
5
48
1
Order By: Relevance
“…The studies of the ion hydration and ion-H 2 O molecule interactions 122,123 demonstrated that ions with smaller size and higher charge density bind H 2 O molecules stronger, which weakens the capacity of helping solvent trap dissolved gas molecules. Anions usually have larger ionic radii than cations, so the hydration of cations is usually much stronger than that of anions 124 323.15 K 62,65,108,111 .…”
Section: Salting Effects Of Different Saltsmentioning
confidence: 99%
“…The studies of the ion hydration and ion-H 2 O molecule interactions 122,123 demonstrated that ions with smaller size and higher charge density bind H 2 O molecules stronger, which weakens the capacity of helping solvent trap dissolved gas molecules. Anions usually have larger ionic radii than cations, so the hydration of cations is usually much stronger than that of anions 124 323.15 K 62,65,108,111 .…”
Section: Salting Effects Of Different Saltsmentioning
confidence: 99%
“…Contrary to the distilled water scenario, the KCl scenario showed an early breakthrough of CO2 albeit an appearance of a gentler curve compared to the others, indicating that the displacement front was wider (Ekwere, 2007) and larger and thus, higher mixing. In terms of solubility, it has been established that CO2 has higher solubility in monovalent salts than divalent salt (Messabeb et al, 2017). Therefore, a possible explanation of this effect observed is that the concentration of the KCl at that ionic strength is higher than the rest, taking into account the nature of the salt.…”
Section: Dispersion Coefficientmentioning
confidence: 99%
“…This drastic shift from moderate KL for divalent brines to high values can be attributed to salting out effects. Salting out effect is defined as the relative reduction of CO2 solubility in aqueous solutions containing salts compared to CO2 solubility in pore water (Messabeb et al, 2017). And divalent salts lead to more salting out than monovalent salts.…”
Section: Figure 5 Co2 Concentration Profile At 2m Ionic Strength For Different Salt Typesmentioning
confidence: 99%
“…Although many data are available in the literature for the CO2 solubility in pure water or single salt solutions, data for carbon dioxide solubility in mixed-salt solutions are still missing. The aim of this study was to use a simple method developed in previous papers [4,5] to determine the carbon dioxide solubility in brines at high temperatures and high pressures.…”
Section: Experimental Determination Of Co2 Solubility In Brines At High Temperatures and High Pressures And Induced Corrosion Of Materialmentioning
confidence: 99%